Present status and future prospects of perovskite photovoltaics - Snaith, H (Nature Publishing Group, 2018)
Solar cells based on metal halide perovskites continue to approach their theoretical performance limits thanks to worldwide research efforts. Mastering the materials properties and addressing stability may allow this technology to bring profound transformations to the electric power generation industry